2017
DOI: 10.1007/s11845-017-1555-6
|View full text |Cite
|
Sign up to set email alerts
|

Parent’s use of the Internet in the search for healthcare information and subsequent impact on the doctor–patient relationship

Abstract: Parents showed a willingness to learn about diseases and treatments, and felt that the Internet was a good resource to do so. This study shows that open discussion about Internet usage between parents and doctors is not common and carers feel at risk of judgment should they admit to Internet usage. The Internet should be seen as a positive adjunct to patient education which can improve understanding, thus strengthening the doctor-patient relationship. The Internet will never replace the role of healthcare prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 15 publications
3
45
3
4
Order By: Relevance
“…An additional 13 studies addressed specific circumstances, mainly prior to a surgical procedure [ 46 - 51 ], after childbirth [ 52 ], 24 hours before an emergency department visit [ 53 ], during stay in a neonatal intensive care unit [ 54 ], in a pediatric outpatient clinic [ 55 , 56 ], in palliative care [ 57 ], and regarding attitudes towards human papillomavirus vaccination [ 58 ]. In addition, 7 studies dealt with general OHIS without specified diseases or particular circumstances [ 14 , 59 - 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An additional 13 studies addressed specific circumstances, mainly prior to a surgical procedure [ 46 - 51 ], after childbirth [ 52 ], 24 hours before an emergency department visit [ 53 ], during stay in a neonatal intensive care unit [ 54 ], in a pediatric outpatient clinic [ 55 , 56 ], in palliative care [ 57 ], and regarding attitudes towards human papillomavirus vaccination [ 58 ]. In addition, 7 studies dealt with general OHIS without specified diseases or particular circumstances [ 14 , 59 - 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only 3 studies explicitly distinguished between general OHIS and specific OHIS [ 36 , 53 , 62 ]. Recent studies from 2017 or later showed the highest prevalences, with around three-fourths [ 51 , 59 , 60 ] to roughly 9 out of 10 parents who searched for health information related to their child [ 14 , 33 , 35 , 44 ]. Likewise, the health-related internet use among parents of children with rare diseases seems to be relatively high [ 44 , 45 ], even for older studies that deal with rare conditions [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The global Internet continues to grow at an exponential rate, bringing with it innovative ways of transacting, communicating, learning, socializing, and transforming just about every aspect of daily life. In addition, the growth of health information on the Internet affects the doctor-patient relationship because of the use of medical information on the Internet (Harvey et al 2017). It is clear that the Internet could change the information-seeking behavior of users and their attitudes.…”
Section: Introductionmentioning
confidence: 99%